Disparity vergence differences between typically occurring and concussion-related convergence insufficiency pediatric patients. (August 2021) - Alvarez, Tara L.; Yaramothu, Chang; Scheiman, Mitchell; Goodman, Arlene; Cotter, Susan A.; Huang, Kristine; Chen, Angela M.; Grady, Matthew; Mozel, Anne E.; Podolak, Olivia E.; Koutures, Chris G.; Master, Christina L.
Highlights: Concussion related convergence insufficiency (PPCS-CI) is different than typically developing (TYP-CI). PPCS-CI has significantly slower vergence peak velocity than TYP-CI. PPCS-CI has more receded near point convergence than TYP-CI. PPCS-CI has more deficient amplitude of accommodation than TYP-CI. Abstract: This study sought to test the hypothesis that significant differences would be observed in clinical measures, symptoms, and objective assessments of vergence eye movements between children with typically developing convergence insufficiency (TYP-CI) and children with persistent post-concussion symptoms with convergence insufficiency (PPCS-CI). Data from age-matched binocularly normal controls (BNC) were used for comparison. Data from three groups of children 11 to 17 years of age are presented: BNC (N = 11), TYP-CI (N = 10), and PPCS-CI (N = 15). Clinical measures of vergence, accommodation, and symptom severity were collected. Symmetrical 4° disparity vergence eye movements were quantified with an eye tracker integrated into a head-mounted display (Oculus DK2). Peak velocity and final response amplitude of convergence and divergence eye movement responses were assessed. The mean near point of convergence (break) was more receded (worse), the amplitude of accommodation more deficient, and convergent and divergent peak velocities slower in the PPCS-CI group compared with the TYP-CI and BNC groups. These results suggest that PPCS-CI may be a different clinical entity than TYP-CI. Hence, more research is warranted to determine whether the therapeutic interventions that are effective for TYP-CI can also be used for PPCS-CI populations.